Implementation of West Java Governor Regulation Number 910/Kep.883- Bapenda/2021 concerning Recipients and Amount of Regional Levy Collection Incentive Payments in West Java - Arenawati, Arenawati (Decision, 2024)
The purpose of this research is to investigate and assess the scope of the Regional Revenue Agency and how taxpayers react to this policy. This study's data analysis consists of data reduction, data display, and generating conclusions. The study's findings demonstrate how the West Java Regional Revenue Agency's deployment of regional tax incentive policies can help to accelerate the response to the impact of Covid-19 and achieve community economic stability. Internal and external variables limit the implementation of regional tax incentives, with internal factors impacted by current conditions at the Regional Revenue Agency and external factors influenced by the community, specifically taxpayers. The findings of this study indicate that various hurdles remain in the implementation of regional tax incentive plans. Based on factors of communication, resources, disposition, and organizational structure.